The first complete mitochondrial genome of Biotodoma cupido (Cichiliformes: Cichlidae) and its phylogeny - Zhang, Xiaoli; Jia, Shuang-Xi; Sun, Cheng-He (Frontiers in Genetics, 2025)
Traditional classifications of New World cichlids have been subject to persistent controversy. Within the genus Biotodoma, only two species are currently recognized; however, complete mitochondrial sequences for these taxa have remained unavailable. In the present study, we sequenced and characterized the complete mitochondrial genome of Biotodoma cupido. This mitogenome has a total length of 16,621 bp and encodes the standard 37 genes found in vertebrate mitochondria: 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and one non-coding control region (D-loop). Among the PCGs, only Cox1 gene utilizes GTG as its start codon, while the remaining 12 PCGs start with ATG. Observed termination codons included TAA, AGA, TAG, and the incomplete codons TA and T. The overall base composition of the B. cupido mitochondrial sequence exhibits an A + T bias, with a combined A + T content of 54.1%. In this study, the high mitogenome similarity observed among several species in this study resulted from interspecific hybridization rather than synonymy or taxonomic misidentification. Maximum likelihood and Bayesian inference evolutionary trees were constructed using mitochondrial genome sequences from 44 Cichlidae species. Phylogenetic analyses consistently recovered the tribes Geophaginae, Cichlasomatinae, and Cichlinae as monophyletic groups. In contrast, the tribe Astronotinae was recovered as polyphyletic. These results clarify the evolutionary position of B. cupido within New World cichlids and will contribute to elucidating the complex phylogenetic relationships among cichlid species.